The dynamics of Pareto distributed wealth in a small open economy - Matthias Birkner; Niklas Scheuer; Klaus Wälde (Economic Theory, 2022)
We study a small open economy with labor, capital accumulation, random death, taxation and a government budget balanced in the long run. We offer methods that provide ordinary differential equations for means and analytical expressions for densities. The latter is achieved by solving stochastic differential equations analytically and deriving the density from this solution. Starting from any distribution, the aggregate distribution converges, both on a transition path towards a steady state and on a transition path towards balanced growth, to a Pareto-distribution. We provide an intuitive economic interpretation for a stationary long-run density with an infinite mean in an economy on a balanced growth path. We also show how government tax policy can lead to non-monotonic links between the equilibrium growth rate of the economy and risk aversion of households.
Keywords: C61; D31; E21; 330; Analytical dynamics of mean and distribution; Wealth; Government budget; Stochastic differential equation